Why are Aedes mosquitoes rare colonisers of Nepenthes pitcher plants? - Chou, L.; Wilson, R.; Dykes, Gary; Clarke, C. (2015)
1. Nepenthes pitcher plants produce fluid-containing animal traps that are colonised by a variety of specialised arthropods, especially dipterans. However, container-breeding vector mosquitoes, such as Aedes albopictus Skuse have rarely been recorded from pitchers. Increasing overlap in the geographical ranges of Nepenthes and Ae. albopictus in urban parts of Southeast Asia owing to urbanisation highlights a growing need to investigate the potential role of pitchers as larval habitats for vector mosquitoes. 2. The ability of Ae. albopictus larvae to survive in three common lowland Nepenthes in Peninsular Malaysia that are most likely to co-occur with Ae. albopictus [viz., Nepenthes ampullaria Jack, Nepenthes gracilis Korth., and Nepenthes mirabilis (Lour.) Druce] was investigated. 3. The larval survival rates of Ae. albopictus in pitcher fluids of the three Nepenthes species were determined, then the effects of low pH, larvicidal agents (such as microbes, predators, and chemical compounds) through manipulative experiments were investigated. 4. It was found that pitchers represent a hostile environment to Ae. albopictus, but that the principal cause of larval mortality varies among Nepenthes species (i.e. low fluid pH in N. gracilis, predation by Toxorhynchites acaudatus Leicester larvae in N. ampullaria, and microbial activity in N. mirabilis). It was concluded that Nepenthes pitchers are generally not suitable larval habitats for Ae. albopictus. However, the pitcher environment of N. ampullaria is worthy of further study, as pitchers that lack predators are nevertheless rarely colonised by Ae. albopictus, indicating that other aspects of the host pitcher environment inhibit oviposition or larval survivorship.